2022
DOI: 10.3390/biom12091270
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanolamine N-Methyltransferase Knockout Modulates Metabolic Changes in Aging Mice

Abstract: Phospholipid metabolism, including phosphatidylcholine (PC) biosynthesis, is crucial for various biological functions and is associated with longevity. Phosphatidylethanolamine N-methyltransferase (PEMT) is a protein that catalyzes the biosynthesis of PC, the levels of which change in various organs such as the brain and kidneys during aging. However, the role of PEMT for systemic PC supply is not fully understood. To address how PEMT affects aging-associated energy metabolism in tissues responsible for nutrie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…In fact, PC could be synthesized via three different pathways: the de novo synthesis Kennedy pathway, the Lands’ cycle, as mentioned above, and the PEMT pathway [ 26 ]. According to animal-level experiment studies, the knockout of PEMT, the critical enzyme for the conversion of PE to PC, resulted in a significant decrease in hepatic PC:PE ratio and insulin resistance [ 10 , 27 , 28 ], suggesting that the changes in PC-PE balance could affect the insulin sensitivity in vivo. And a deficiency of muscle CEPT1, the terminal enzyme for de novo synthesis of PC in the Kennedy pathway, resulted in a significant reduction of two diacyl-PEs and an significant increase in three diacyl-PCs containing docosahexaenoic acyl (DHA) or arachidonic acyl (AA) moieties in muscle endoplasmic reticulum, and improved insulin sensitivity in high-fat-diet mice [ 9 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PC could be synthesized via three different pathways: the de novo synthesis Kennedy pathway, the Lands’ cycle, as mentioned above, and the PEMT pathway [ 26 ]. According to animal-level experiment studies, the knockout of PEMT, the critical enzyme for the conversion of PE to PC, resulted in a significant decrease in hepatic PC:PE ratio and insulin resistance [ 10 , 27 , 28 ], suggesting that the changes in PC-PE balance could affect the insulin sensitivity in vivo. And a deficiency of muscle CEPT1, the terminal enzyme for de novo synthesis of PC in the Kennedy pathway, resulted in a significant reduction of two diacyl-PEs and an significant increase in three diacyl-PCs containing docosahexaenoic acyl (DHA) or arachidonic acyl (AA) moieties in muscle endoplasmic reticulum, and improved insulin sensitivity in high-fat-diet mice [ 9 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive Ca 2+ activates calpains that cleave autophagy‐related proteins, such as ATG5, thus inhibiting mitochondrial autophagy. [ 124 ] In addition, this complex may regulate atrial remodeling by regulating calcium interaction between the ER and mitochondria.…”
Section: The Role Of Organelle Interactions In Disease and Therapymentioning
confidence: 99%
“…Evidence indicates that dysregulated lipid metabolism contributes to aging via various mechanisms [113][114][115]. Zhou et al [116] demonstrated that the absence of PEMT increases the divergence of the metabolome during the aging process of the gastrointestinal tract and liver. The vulnerability of the brain increases rapidly with age, and the lipid fatty acid composition of the brain membrane changes with age [117].…”
Section: Pemt and Agingmentioning
confidence: 99%